2019
DOI: 10.1007/978-3-030-29933-0_27
|View full text |Cite
|
Sign up to set email alerts
|

Improving Session Based Recommendation by Diversity Awareness

Abstract: Recommender systems help users to discover and filter new and interesting products based on their preferences. Session-Based Recommender systems are powerful tools for anonymous e-commerce visitors to understand their behaviours and recommend useful products. Diversity in the recommendations is an important parameter due to increasing the opportunity of recommending new and less similar items that users interacted. Effect of diversity has been investigated in many works for the collaborative filtering-based Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…Anelli et al [55] introduced a variant of xQuAD in which they changed the diversity component in the greedy optimization approach of xQuAD to make it time and session aware. Esmeli et al [56] introduced a variant of IKNN using not only the last item but also the session context in score calculations. They also used the dissimilarity of recommendable items based on the whole session items in the final score function.…”
Section: Boosting Accuracy and Diversity In Session-based Recommendermentioning
confidence: 99%
“…Anelli et al [55] introduced a variant of xQuAD in which they changed the diversity component in the greedy optimization approach of xQuAD to make it time and session aware. Esmeli et al [56] introduced a variant of IKNN using not only the last item but also the session context in score calculations. They also used the dissimilarity of recommendable items based on the whole session items in the final score function.…”
Section: Boosting Accuracy and Diversity In Session-based Recommendermentioning
confidence: 99%
“…Nowadays, users' spend more time on exploring different products and comparing products in different ecommerce platforms to find the most advantageous one in terms of price and quality [8]. Many well-known e-commerce platforms record users' activities and use this data to have personalised content by giving recommendations [13], [14], and purchase prediction in the sessions [43], [44].…”
Section: Related Work a Session Logsmentioning
confidence: 99%
“…SBRS has a growing trending since their success in providing real-time recommendations even to anonymous users. Many SBRS models are designed [17], [23], [18], [13], [14]. Authors [17] designed RNN based recommendation for short user interaction history their results on Yoochose dataset 1 showed their designed method showed the superiority over the Item-Item similarity-based recommendation.…”
Section: B Session Based Recommendationmentioning
confidence: 99%
“…One of the ways of re-ranking is taking into account the diversity awareness of the recommended items [21]- [23]. [21] designed a diversity aware re-ranking framework for the session-based recommendation, in which the ranking score of recommended items is updated as based on the results of the diversity level between last interacted item of the session and recommended items. They found that when re-ranking is applied, the RS model produced better performance in terms of recall and precision.…”
Section: B Re-ranking In Recommender Systemsmentioning
confidence: 99%
“…In this work, we applied a re-ranking approach using a linear regression model on the recommendation list for next item prediction. Re-ranking approaches have been applied in different works [21]- [23], [25], [27], [38] where context-awareness, diversity and popularity based re-ranking options have been used. In this work, we applied a linear regression model to re-rank given the candidate recommendation list, and predict an interest level for recommended items based on multiple factors such as users' behaviours in users' previous sessions and recommended items' features.…”
Section: Conclusion and Future Directionmentioning
confidence: 99%